Czy Mussolini był butny? Refleksje wokół pewnej biografii Benita Mussoliniego - Sondel-Cedarmas, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The article is a review of a book by the Swedish writer and journalist Göran Hägg entitled Mussolini. En studie i makt published in Poland in 2015 as Mussolini. Butny faszysta [Mussolini. An Arrogant Fascist]. By focusing on elements which distinguished Mussolini’s dictatorship from Adolf Hitler’s Third Reich and Joseph Stalin’s Soviet Union, Hägg subscribes to the view, present in contemporary historiography, that the Italian version of totalitarianism was “incomplete”. Stressing the mass support for the regime in 1925–1936, the author links the Duce’s gradual fall from power to mistakes in internal and foreign policy in the second half of the 1930s, especially to the adoption of the racist laws of 1936 as well as Italy’s accession to the Anti-Comintern Pact and participation in the Second World War on Germany’s side. What the author considers to have been unquestionably misguided moves which sealed the fate of the Italian leader on 25 April 1945 were his decisions taken during the existence of the Italian Social Republic, namely: 1 creation of internment and concentration camps for Italian Jews; 2 ruthless fight against the anti-fascist resistance movement; and 3 massacres of civilians by SS troops and fascist republicans in northern Italy in 1944–1945.
Keywords: Mussolini, Benito (1883-1945); faszyzm; Hägg, Göran; Włoska Republika Socjalna